Effects of endosperm type on nutritional value of sorghum grain for swine - G L Allee; K Smith (Kansas Agricultural Experiment Station Research Reports, 1973)
Two feeding trials, a digestion trial, and a preference trial were conducted to evaluate the effects of endosperm type on the nutritional value of sorghum grain in swine diets. Endosperm types evaluated were: (1) white endosperm–red seed coat;(2) Heterozygous yellow endosperm–bronze seed coat; (3) homozygous yellow endosperm–yellow seed coat. In trial I, 63 pigs averaging 47 pounds were used in a 28-day experiment. Performance of pigs in trial I was not influenced by endosperm type. A digestion study using 51 pound pigs showed endosperm type making no significant difference in protein digestibility or nitrogen retention. Trial II involved 81 finishing pigs averaging 125 pounds. Pig performance as measured by daily gain, feed per pound of gain, and carcass measurements was not influenced by endosperm type. The results indicate that the endosperm type studied did not affect pig performance.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Endosperm; Nutritional value; Sorghum grain; Peformance